Dermal Uptake of Organic Vapors Commonly Found in Indoor Air - Weschler, Charles J; Nazaroff, William W (Environmental science & technology, 2014)
Transdermal uptake directly from air is a potentially important yet largely overlooked pathway for human exposure to organic vapors indoors. We recently reported (Indoor Air 2012, 22, 356) that transdermal uptake directly from air could be comparable to or larger than intake via inhalation for many semivolatile organic compounds (SVOCs). Here, we extend that analysis to approximately eighty organic compounds that (a) occur commonly indoors and (b) are primarily in the gas-phase rather than being associated with particles. For some compounds, the modeled ratio of dermal-to-inhalation uptake is large. In this group are common parabens, lower molecular weight phthalates, o-phenylphenol, Texanol, ethylene glycol, and α-terpineol. For other compounds, estimated dermal uptakes are small compared to inhalation. Examples include aliphatic hydrocarbons, single ring aromatics, terpenes, chlorinated solvents, formaldehyde, and acrolein. Analysis of published experimental data for human subjects for twenty different organic compounds substantiates these model predictions. However, transdermal uptake rates from air have not been measured for the indoor organics that have the largest modeled ratios of dermal-to-inhalation uptake; for such compounds, the estimates reported here require experimental verification. In accounting for total exposure to indoor organic pollutants and in assessing potential health consequences of such exposures, it is important to consider direct transdermal absorption from air.